Clinicopathological Characteristics of Cutaneous Melanocytic Lesions for Predicting Biological Behavior: 5 Years Retrospective Study in National Referral Hospital - Rosari, Bayu Perkasa; Arisanty, Riesye (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2025)
Background Cutaneous melanocytic lesions have variety of subtypes ranging from benign (nevus) to malignant lesions (malignant melanoma). Differentiating benign and malignant melanocytic lesions is challening, particularly due to overlapping characteristics. This study was conducted to determine clinicopathological characteristics of cutaneous melanocytic lesions and the prevalence ratio of each characteristic for predicting malignant behavior. Method Cross-sectional study was conducted with data retrieved from Anatomic Pathology Department of Faculty of Medicine Universitas Indonesia and Dr. Cipto Mangunkusumo Hospital. Data of 145 histopathology-confirmed cutaneous melanocytic lesions cases between 2018 – 2022 were sampled and collected. Bivariate analysis was used to determine the prevalence ratio of each characteristic to predict malignant behavior. Result Out of 145 cases, 14.5% were malignant lesions (melanoma) and the rest were benign (nevus). Clinicopathology features and characteristics were correlated with malignant behavior, such as cytological atypia (p <0.01), dermal mitosis (PR=91.5; p<0.01), asymmetry (PR=31.8; p <0.01), suprabasal melanocyte (PR=21.4; p <0.01), lower extremity location (PR=6.5; p <0.01), sized >6 mm (PR=5.2; p <0.01), and male gender (PR=3.3; p <0.01). Conclusion Clinicopathological characteristics of cutaneous melanocytic lesions such as cytological atypia, dermal mitosis, asymmetry, suprabasal melanocyte, lower extremity location, sized >6 mm, dermal lymphocytic infiltrate, and male gender were predictive to predict malignant lesions.